Chemometrics in Electroanalysis - Díaz-Cruz, José Manuel; Esteban, Miquel; Ariño, Cristina; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This monograph covers the most relevant applications of chemometrics in electrochemistry with special emphasis on electroanalytical chemistry. It reviews the use of chemometric methods for exploratory data analysis, experimental design and optimization, calibration, model identification, and experts systems. The book also provides a brief introduction to the fundamentals of the main chemometric methods and offers examples of data treatment for calibration and model identification. Due to the comprehensive coverage, this book offers an invaluable resource for graduate and postgraduate students, as well as for researchers in academic and industrial laboratories working in the area of electroanalysis and electrochemical sensors.
Introduction -- Main characteristics and types of electrochemical data -- Exploratory data analysis -- Experimental design and optimization -- Calibration -- Model identification -- Expert systems in electroanalysis. .
Keywords: Electrochemistry; Analytical chemistry; Chemistry -- Data processing; Electrochemistry; Analytical Chemistry; Computational Chemistry